2018
DOI: 10.1152/ajprenal.00420.2017
|View full text |Cite
|
Sign up to set email alerts
|

Intermittent hypoxia exacerbates increased blood pressure in rats with chronic kidney disease

Abstract: Kidney injury and sleep apnea (SA) are independent risk factors for hypertension. Exposing rats to intermittent hypoxia (IH) to simulate SA increases blood pressure whereas adenine feeding causes persistent kidney damage to model chronic kidney disease (CKD). We hypothesized that exposing CKD rats to IH would exacerbate the development of hypertension and renal failure. Male Sprague-Dawley rats were fed a 0.2% adenine diet or control diet (Control) until blood urea nitrogen was >120 mg/dl in adenine-fed rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
9
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 44 publications
2
9
0
1
Order By: Relevance
“…Hypertension is a leading risk factor for the initiation and progression of CKD as well as a consequence of CKD. Using adenine oral administration to cause CKD in rats, we previously demonstrated that CKD and IH additively elevate blood pressure, but IH does not enhance adenine-induced renal fibrosis, inflammation, and decline of kidney function (31). In the same study, pre-pro-ET-1 mRNA levels were increased in the renal cortex and medulla of CKD rats, whereas IH did not further enhance ET-1 expression (31).…”
Section: Introductionmentioning
confidence: 85%
See 4 more Smart Citations
“…Hypertension is a leading risk factor for the initiation and progression of CKD as well as a consequence of CKD. Using adenine oral administration to cause CKD in rats, we previously demonstrated that CKD and IH additively elevate blood pressure, but IH does not enhance adenine-induced renal fibrosis, inflammation, and decline of kidney function (31). In the same study, pre-pro-ET-1 mRNA levels were increased in the renal cortex and medulla of CKD rats, whereas IH did not further enhance ET-1 expression (31).…”
Section: Introductionmentioning
confidence: 85%
“…CKD model induction and prevention assessment protocol. CKD was induced by feeding rats 0.2% adenine (Sigma-Aldrich) mixed in Nutra-gel (Bio Serv) for 2 wk (31), which is equivalent to a dose of 40 g•rat Ϫ1 •day Ϫ1 . Rats in CKD and control groups assigned to concurrent macitentan received 30 mg•kg Ϫ1 •day Ϫ1 in the same food.…”
Section: Prevention Studymentioning
confidence: 99%
See 3 more Smart Citations